THE ALGORITHM OF ANALYTHING ENGLISH TEXTS WITH THE HELP OF PARSERS - Парнус, Катерина; Свісюк, Олена (SWorldJournal, 2022)
The need for a scientific study of the algorithm for processing English-language text using parsers is relevant for the study of grammatical structures by students in English-language texts of modern society. The purpose of the study is to justify the met